Whole-body vibration and balance training: A proprioceptive overload? - Lindley, S.; May, K.; Richards, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Whole-body vibration training (WBVT) is a neuromuscular training method that has recently been popularised and integrated into many conditioning programs. WBVT and balance training have also been used in combination as a rehabilitation and injury prevention modality (Rittweger, 2010). However, little work has investigated the effects of WBVT on the motor control system. This study explores the effects of combined Vibration Training and Balance Training using the Vibrosphere and its efficacy within an applied or clinical setting. Methods: Subjects (n=10) participated in a single testing session consisting of 5 single dominant leg dips pre and post each intervention. The randomised interventions were standing in a double leg mini squat position for 30 seconds; on 1) Vibrosphere placed on a mat with the vibration at 45 Hz, 2) Vibrosphere on a mat without vibration, 3) on a soft mat, and 4) laboratory hard floor. 3D Joint kinematics of the Ankle, Hip and Knee joint were captured using a 10-camera Qualisys camera system and modelled using the CAST technique. Results: A significant increase in the knee and hip joint angular velocities was seen in the coronal plane (-5.3 deg/s and 8.6 deg/s) and a significant decrease in sagittal knee joint velocity (5.3 deg/s) were found following the vibration intervention. Discussion: The increase in the coronal plane knee and hip joint velocities could contribute to additional medial and internal rotation stresses upon soft tissue structures. This is not in agreement with other studies (Moezy et al., 2008) who have found WBVT to be a beneficial neuromuscular modality in injury prevention and rehabilitation. However previous research has not considered joint angular velocities, which are important variables in the control and stability. The increase in instability following the vibration intervention is thought to be caused by an overload to the proprioceptive receptors, therefore affecting the control mechanisms. Clinicians should consider the effects of vibration on the proprioception system and consequent joint control within the design of their rehabilitation or conditioning programs.